Geological characteristics and exploration potential of the coal measure gas from Shan 2 of the Shanxi formation in the eastern Ordos Basin - Zhao, Wei-Bo; Zhang, Hui; Shi, Yun-He; Fu, Xun-Xun; Hui, Jie; Jing, Xue-Yuan (Frontiers in Earth Science, 2023)
Coal measure gas, excluding tight (low-permeability) sandstone gas, specifically refers to the self-sourcing unconventional natural gas stored in coal, shale, and fine siltstone in this study, characterized by various types of occurrences and reservoirs, a distinct cyclic succession of coal measure strata, widely distributed and mosaic hydrocarbon accumulations, the three coal gas accumulations, and configurations of vertically multiple stacked gas-bearing reservoirs. According to the grain size of sandstone, configurations of sandstone-coal-mudstone association, thickness, and layers, coal measure gas from Shan 2 can be divided into four types of thick massive sandstone-coal-mudstone (type I), fine siltstone-coal-mudstone (type II), thin sandstone-mudstone-sandstone (type III), and coal-mudstone (type IV). The comprehensive evaluations suggest that coal measure gas in the Suide-Mizhi area of the southern Ordos basin opens up an important and favorable accumulation option, characterized by having coalbed methane, shale gas, and tight gas stored in sandstone-mudstone-coal strata. Therefore, it is essential to require full future assessments for the coal beds, shale, and tight gas controlling exploration with the purpose of “vertical gas-bearing zone”, by using the three-dimensional exploration strategy.